HUBUNGAN KOMPETENSI GURU DAN IKLIM KERJA DENGAN KINERJA GURU SD NEGERI - Sarwan, Sarwan; Taena, La; Karno, Edy (Jurnal Wahana Kajian Pendidikan IPS, 2019)
Abstract: The purpose of this study was to study and analyze 1) The Relationship of Competencies with the Performance of Public Elementary Teachers in Unaaha District, Konawe Regency. 2) Relationship of Work Climate with Performance of Public Elementary Teachers in Unaaha District, Konawe Regency and 3) Relationship between Work Competency and Work Climate with the performance of teachers of Public Elementary Teachers in Unaaha District, Konawe Regency. The method used in this study is a survey method using the correlational method. The results of the study found that: 1) There was a positive and significant relationship between teacher competency and the performance of teachers of Public Elementary Schools in Unaaha District, Konawe District, as enhanced by a regression coefficient of 0.780 and a coefficient of determination of 0.608; 2) There is a positive and significant relationship between work climate and teacher performance in public elementary schools in Unaaha Subdistrict, Konawe Regency, as enhanced by a regression coefficient of 0.762 and a coefficient of determination of 0.581; 3) There is a positive and significant relationship between teacher competency and the performance of SD Negeri teachers in Unaaha Subdistrict, Konawe District, as shown by the regression coefficient of 0.843 while the coefficient of determination is 0.711.Keywords: Teacher Competency; Work Climate; Teacher Performance